Influence of the characteristics of Machine-Tool-Fixture-Work (MTFW) system on chatter - Amin, A. K. M. Nurul (1985)
Experiments have been carried out to determine the influence, of different elements of MTFW system on the frequency and. amplitude of chatter and on the ranges of cutting speeds where chatter exists. It has been established that, at definite ranges of cutting speeds metal cutting process is accompanied with chatter. When either spindle work system or tool obit holder vibrates with their natural frequencies. Source of such chatter is the unstability of metal cutting process at all cutting speeds with frequencies which is directly, proportional to cutting speed. Dependence of the frequencies of chatter, when resonance occurs, on cutting speed is defined by straight tines, either parallel to or a bit inclined with the axis of cutting speed. Frequency level and amplitude of such chatter and extent of the ranges of cutting speed, where it exists depend mainly on the rigidity of spindle-work system for low frequency chatter and on the rigidity of tool-bit holder for medium frequency chatter.